Gasifier, Solid Oxide Fuel Cell Integrated Systems for Energy Production From Wet Biomass - Recalde, Mayra; Woudstra, Theo; Aravind, P. V. (Frontiers in Energy Research, 2019)
Nowadays, there is worldwide interest in diversifying energy supply. In this regard, biomass is the best possible renewable organic substitute for fossil fuels. In particular, the energy content of very wet biomass, recovered with appropriate technology, could potentially be used for power generation. In addition to power generation, this technology would represent a sanitary option to improve the quality of public health and the environment. Supercritical water gasification (SCWG) is a technology applied for the conversion of wet biomass into gas. It uses the specific physical properties of water at supercritical conditions to decompose the organic matter. However, near 100% conversion, close to thermodynamic equilibrium, of real biomass into gas is not yet demonstrated. The conversion is higher at dry biomass concentrations below 10 wt.%, but at these conditions, the system is not energetically sustainable. The conversion depends on the SCWG operating conditions and the properties of the catalyst. Because of present-day technical limitations, the conversion efficiency in SCWG is low when fed with real biomass. The net electrical efficiency of a combined system SCWG—solid oxide fuel cell (SOFC), fed with fecal sludge at 15 wt.% dry biomass, reaches between 50 and 70% (thermodynamically calculated values), whereas utilizing an SCWG designed with present-day engineering gives 29–40%. The SOFC fuel utilization influences the system efficiency significantly, as the processed heat available for the heat integration depends on fuel utilization. The extreme operating conditions of an SCWG-based system cause technical limitations toward reaching complete conversion during gasification. An efficient and stable catalyst is not yet available at competitive costs for low-temperature SCWG of real biomass. Intensive research in different gasification-SOFC system configurations that include the integration of complementary processes, such as the electrochemical oxidation of higher hydrocarbons or the electrochemical reduction of CO2 and H2O, will increase the potential of the gasification–SOFC system for commercialization in medium scale in the future and become a technology that provides economic, environmental, and health benefits.